Intervening Effect of Hybrid Method in Enhancing Secondary Teachers’ Engagement and Satisfaction in Angeles City - Jennifer H. Operio (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
This inquiry was an attempt to probe the intervening effect of technology expressed as the hybrid method or approach in enhancing teachers’ engagement and satisfaction in imparting knowledge to Senior High School. Descriptive-quantitative research was utilized. Fifty senior high school teachers teaching Accountancy, Business, and Management (ABM) strand students are targeted. However, only 35 filled-out survey forms were turned in. The application or homogenization of technology in educating the learners at the Senior Secondary level was recognized. Ethical considerations were employed in conducting this research; they were: respect for anonymity and confidentiality of the information collected; respect for privacy – respondents were given ample time to answer the survey questionnaire; they were protected in such a way that they did not feel intimated, the proponent let another person conduct the survey and was not directly involved with the distribution and collection of the survey instrument. Results show that though teachers utilized the hybrid approach, a small percentage of them still fully utilized the traditional approach in providing information to their learners. Scientific progressions in technology have their own opportunities and challenges. Probing could be made to have coequality for all sets of learners on the implementation of computerization and automation to the ongoing pedagogy in the absence of permitting the ardent method of conveying what the essentials are. As a recommendation, further research could be triangulated, which will involve students and school administrators to further validate the mediating effect of hybrid learning on students' engagement.